PEMATAHAN DORMANSI BENIH SENGON (Falcataria moluccana) DENGAN SKARIFIKASI MEKANIK - Irmayanti, Laswi; Nurdin, Aqshan Shadikin; Rangkuti, Ahmad Baiquni; Rambey, Ridahati; Nurhikmah, Nurhikmah; Ashari, Reyna; Anwar, Arniana; Nurjannah, Siti (Universitas Lambung Mangkurat, 2023)
Sengon (Falcataria moluccana) is a legume that generally has physical dormancy. Physical dormancy causes slow seed germination if the dormancy is not broken properly. Many studies have been reported regarding dormancy breaking treatment with hot water on sengon seeds, but rarely use mechanical scarification treatment. The purpose of this study was to examine the effect of mechanical scarification on sengon seed germination. The experimental design used was a one-factor Completely Randomized Design (CRD). The factors used were the mechanical scarification technique (3 treatments), namely P1: control, P2: pricking the seed with a needle, and P3: cutting the tip of the seed. The germination parameters used were the percentage of germination (PK), peak value (PV), average daily germination (MDG), and germination value (NK). The results showed that the PK values for each treatment were P1 = 55%, P2 = 75%, and P3 = 72%. The PV values were P1=15.18, P2=17.75, and P3=17.53. The MDG values were P1=0.92, P2=1.25, and P3=1.20. The NK values were P1=13.90, P2=22.28, and P3=22.13. P2 treatment (needle prick) gave the highest response on all parameters of sengon germination. Based on the results of the Analysis of Variance (Anova), it was found that the treatment had a significant effect on the parameters PK, MDG, and NK. While the PV parameters showed no significant difference.